GEO-LOCATION OF TRANSMITTERS USING REAL DATA, DOPPLER SHIFTS AND LEAST SQUARES - Tobler de Sousa, Cristina; Koiti Kuga, Hélio; Setzer, Alberto W. (Acta astronautica, 2003)
We describe a new method implemented at INPE (Brazilian Space Research Institute) for obtaining the geographic location of transmitters, using Doppler shifts and a batch estimator based on least-squares technique. Near real-time geographical location of transmitters through satellite can be useful for many applications, such as to monitor and rescue people in remote areas, and to track animals and oceanographic buoys for scientific research. A representative data set used for the tests was collected by means of a portable reception station located in the Antarctic Brazilian Station (Antarctica), using the NOAA-12 satellite as data relay, and a transmitter placed in the nearby Elephant Island. In addition, we obtained data collected in Cuiaba Satellite Reception Station (Central Brazil) using the Brazilian satellite SCD-2 and a nearby Data Collecting Platform transmitter. This paper addresses the modeling of the Doppler shift measurements, the satellite dynamic motion, and the non-linear least squares technique applied to the problem. The results and analysis of the geo-location method are shown and depicted here, demonstrating the location accuracy of 3.13#+1.51 km and 2.74#+2.41 Km for the two data sets respectively, achieved by such a near real-time system.